Inadequacy of air purifier for indoor air quality improvement in classrooms without external ventilation. (January 2022) - Choe, Youngtae; Shin, Jun-shup; Park, Jinhyeon; Kim, Eunchae; Oh, Narae; Min, Kihong; Kim, Dongjun; Sung, Kyunghwa; Cho, Mansu; Yang, Wonho
Abstract: School classrooms are one of the most densely populated indoor environments. Students are likely to be exposed to indoor air pollutants because they spend most of their time in the classroom. Consequently, indoor air quality (IAQ) management in classrooms is essential. Air purifiers have been installed in all school classrooms by the Ministry of Education in Korea because of concerns regarding particulate matter (PM). This study assessed the IAQ in school classrooms and suggested IAQ management methods. Sensor-based instruments were installed in each test classroom to measure the PM and carbon dioxide (CO2 ) concentrations on weekdays over six months in 2019. The PM10 (PM of 10 μm or less in diameter) concentration in the classroom was <75 μg/m 3, which is the Korean School Health Act standard. However, the average concentration of PM2.5 was higher than the standard concentration of 35 μg/m 3 . The air purifiers reduced the PM concentration in school classrooms by approximately 30%, thereby satisfying the Korean PM standards. However, the CO2 concentrations in most classrooms exceeded 1000 ppm, thereby indicating an insufficient ventilation rate. Considering the perceived IAQ according to satisfaction and health effects, students felt that they were significantly more affected by CO2 than PM in the classrooms. Graphical abstract: Image 1 Highlights: Particulate matter (PM) has recently emerged as a social problem in Korea such as installing air purifiers in all schools. The air purifiers reduced the concentration of PM by approximately 30%; however, showed a lack of ventilation. Contribution rates to total PM by indoor PM generation in school classrooms were higher than those outdoors. Students' perception of indoor air quality showed a significant correlation with CO2 concentrations rather than those of PM.